Government ideology in donor and recipient countries: Does political proximity matter for the effectiveness of aid? - Axel Dreher; Anna Minasyan; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2013)
Political proximity between donor and recipient governments may impair the effectiveness of aid by encouraging favoritism. By contrast, political misalignment between donor and recipient governments may render aid less effective by adding to transaction costs and giving rise to incentive problems. We test these competing hypotheses empirically by considering the political ideology of both governments along the left-right spectrum in augmented models on the economic growth effects of aid. Following the estimation approach of Clemens et al. (2012), we find that aid tends to be less effective when political ideology differs between the donor and the recipient.
Keywords: O19; O11; F35; F53; 330; aid effectiveness; economic growth; politics and aid; government ideology